Endocardial Peripheral Nerve Sheath Tumour with Features of a Benign Schwannoma in a Donkey. Issue 4 (November 2017) - Paraschou, G.; Suárez-Bonnet, A.; Grove, V.; Priestnall, S.L.
Summary: A peripheral nerve sheath tumour, with features of a benign schwannoma and arising from the endocardium of the right ventricle, was found incidentally during routine post-mortem examination of a 28-year-old gelding donkey. Macroscopically, five round to oval, white to grey and red, firm masses, firmly attached to the endocardium were identified. Microscopically, the endocardium and adjacent subendocardium were infiltrated by a variably demarcated, non-encapsulated mesenchymal neoplasm with features of a benign schwannoma, including concurrent presence of Antoni A and Antoni B areas, nuclear palisading, neoplastic cells with enlarged bizarre nuclei ('ancient change') and the formation of Verocay-like bodies. Immunohistochemically, the tumour cells were variably strongly positive for expression of S100 and glial fibrillary acidic protein. This is the first cardiac tumour reported in a donkey and is macroscopically, histologically and immunohistochemically similar to endocardial schwannoma occurring in Wistar rats.